2017
DOI: 10.1001/jamapediatrics.2017.0460
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Ponderal Mass Index vs Body Mass Index in Estimating Body Fat During Adolescence

Abstract: IMPORTANCE Body mass index (BMI) is used to diagnose obesity in adolescents worldwide, despite evidence that weight does not scale with height squared in adolescents. To account for this, health care providers diagnose obesity using BMI percentiles for each age (BMI z scores), but this does not ensure that BMI is accurate in adolescents.OBJECTIVE To compare the accuracy of BMI vs other body fat indices of the form body mass divided by height n in estimating body fat levels in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
238
4
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(259 citation statements)
references
References 21 publications
11
238
4
6
Order By: Relevance
“…In the absence of waist circumference data, we used the TMI, a new parameter found to estimate body fat levels more accurately than BMI, as first described by Peterson et al In our cohort, TMI values were found to be significantly higher among those with multiple cardiometabolic risk factors, clearly indicating that these patients had increased fat mass levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the absence of waist circumference data, we used the TMI, a new parameter found to estimate body fat levels more accurately than BMI, as first described by Peterson et al In our cohort, TMI values were found to be significantly higher among those with multiple cardiometabolic risk factors, clearly indicating that these patients had increased fat mass levels.…”
Section: Discussionmentioning
confidence: 96%
“…BMI was calculated as weight in kilograms divided by height in meters squared. Tri‐ponderal mass index (TMI) was calculated as weight divided by height cubed.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Nevill et al demonstrated that scaling WC to body size was more accurate than traditional methods of predicting metabolic risk indicators in adults. Further, it was recently suggested that the tri‐ponderal index (TPI) should be a more accurate surrogate of body fat, and since body fat is strongly related to metabolic risk, the TPI could more suitably describe the association with metabolic risk indicators in the paediatric population. Thus, the purpose of the present study was to investigate the association of six different anthropometric markers (BMI, BMI z‐score, TPI, WC, WC/H, and WC/H adj ) with metabolic syndrome in children and adolescents to find the best suited index to predict metabolic risk.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BMI itself might not be a suitable criterion in early childhood, a period characterized by rapid growth. The accuracy of other body fat indices such as youth triponderal mass index, which was introduced to estimate the fat level in young children, has not been confirmed . Secondly, the study outcome was obesity at age 15 years only, and did not include diabetes or other cardiovascular outcomes in adulthood, which would have required a much longer follow‐up period.…”
Section: Discussionmentioning
confidence: 99%